Effect on Opioids Requirement of Early Administration of Intranasal Ketamine for Acute Traumatic Pain. Issue 6 (June 2020) - Bouida, Wahid; Bel Haj Ali, Khaoula; Ben Soltane, Houda; Msolli, Mohamed Amine; Boubaker, Hamdi; Sekma, Adel; Beltaief, Kaouthar; Grissa, Mohamed Habib; Methamem, Mehdi; Boukef, Riadh; Belguith, Asma; Nouira, Semir
Abstract : Objectives: To evaluate the efficacy and safety of early administration of low-dose intranasal ketamine on reducing the need for opioid and nonopioid analgesic agents in emergency department (ED) patients with acute moderate to severe acute limbs' trauma pain. Patients and Methods: This is a double-blind, randomized, prospective, controlled study conducted in the ED. The included patients were randomly assigned to intranasal pulverization of ketamine or placebo. Protocol treatment was given at the triage. The primary outcome is the need for opioids during ED stay. Secondary outcome included the requirement of nonopioid analgesic agents and the percentage of patients discharged from the ED with a visual analog scale (VAS) <30. A combined outcome score including the 3 outcome items was constructed. Results: The authors included 1102 patients, 550 patients in the placebo group, and 552 in the intranasal ketamine group. The groups were similar regarding demographics, clinical characteristics, and baseline VAS. The need for opioids was decreased in the intranasal ketamine group compared with the placebo group (17.2% vs. 26.5%; P <0.001). The need for nonopioid analgesics was significantly lower in the intranasal ketamine group compared with the placebo group (31.1% vs. 39.6%; P =0.003). The percentage of patients discharged with a VAS score <30 was significantly higher in the intranasal ketamine group ( P <0.001). The mean combined outcome score was 0.97 in the placebo group and 0.67 in the intranasal ketamine group ( P <0.001). Conclusion: Intranasal ketamine administered early in the triage was associated with a decrease in opioids and nonopioid analgesics need in patients with acute limb trauma-related pain.